Molecular and Phytochemical characterization of Andrographis paniculata Nees in Thirunelveli Hills in South India - G.S., REKHA; A., JOHN DE BRITTO (Malaysian Journal of Science, 2010)
In the present study, Andrographis paniculata Nees was collected from ten locations in Tirunelveli hills and the genetic variability was investigated using RAPD-PCR fingerprint and the population which showed high percentage of polymorphism was selected. Those populations were chosen for further phytochemical analysis. The active principle in these plants has been quantified by HPLC analysis. The population which exhibited both high percentage of polymorphism and high amount of active principle was considered to be the superior genotype.